2021
DOI: 10.20344/amp.12998
|View full text |Cite
|
Sign up to set email alerts
|

Adult Native Joint Septic Arthritis: A Nine-Year Retrospective Analysis in a Portuguese University Hospital

Abstract: Introduction: Septic arthritis of a native joint represents a medical emergency. Drainage and effective antibiotic treatment are critical to avoid joint destruction and long-term impairment. The aim of this study was to evaluate epidemiological and clinical characteristics of patients with the diagnosis of septic arthritis to help establish local guidelines for empirical antibiotic treatment.Material and Methods: Retrospective analysis of adult patients admitted at Centro Hospitalar Universitário do Porto from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…S. aureus remains a challenging pathogen to diagnose in septic arthritis, with modern methods failing to reach the performance necessary to identify it in time to reduce morbidity and mortality. Patients with risk factors such as diabetes and tobacco usage are at increased risk of infection and severity [ 15 , 17 , 18 ]. In addition to diagnostic method improvements, preventative research is also needed to mitigate morbidity associated with patients like ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. aureus remains a challenging pathogen to diagnose in septic arthritis, with modern methods failing to reach the performance necessary to identify it in time to reduce morbidity and mortality. Patients with risk factors such as diabetes and tobacco usage are at increased risk of infection and severity [ 15 , 17 , 18 ]. In addition to diagnostic method improvements, preventative research is also needed to mitigate morbidity associated with patients like ours.…”
Section: Discussionmentioning
confidence: 99%
“…Balato et al found that culture negative infections have been reported to range from 16.7% to 78.4% [ 14 ]. A nine-year retrospective analysis at a single center in Portugal by Cipriano et al, with predominantly S. aureus septic arthritis, noted that only 50.5% of arthrocentesis cultures had positive growth in synovial fluid [ 15 ]. Another retrospective study by Daynes et al analyzing 183 cases of native joint infections found that joint fluid cultures were positive in 55% of cases; and of these cases, blood cultures yielding the same pathogen were found in 54% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causative organisms in this study were predominantly Gram-positive bacteria, with S. aureus and Streptococci attributable for more than 80% of these cases. MRSA was accountable for septic arthritis in more than half of the patients with bacteremia (58.3%) and in almost half of the patients who had positive synovial fluid cultures (47.6%)—both of these prevalence rates were higher than that of the general population [ 4 , 28 , 29 ]. The incidence rate of MRSA infection in dialysis patients in this study is noticeably higher than the rates reported in septic arthritis studies with or without dialysis status [ 9 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRSA was accountable for septic arthritis in more than half of the patients with bacteremia (58.3%) and in almost half of the patients who had positive synovial fluid cultures (47.6%)—both of these prevalence rates were higher than that of the general population [ 4 , 28 , 29 ]. The incidence rate of MRSA infection in dialysis patients in this study is noticeably higher than the rates reported in septic arthritis studies with or without dialysis status [ 9 , 29 , 30 ]. A higher risk of MRSA bacteremia in dialysis patients along with increased incidence of MRSA infections in both healthcare and community settings may explain this difference [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%